Viability of obtaining microencapsulated and lyophilized acerola pulp (malpighia spp): A review (Research, Society and Development, 2021)
The purpose of this review is to provide a deep understanding of the techniques that induce the quality processing of acerola and the preservation of its bioactive compounds. It was possible to conclude that acerola is a fruit with great antioxidant potential, due to its bioactive compounds, requiring the application of technologies such as microencapsulation and lyophilization to preserve them. Further studies are needed to assess the behavior of acerola pulp in different application parameters, in addition to performing physical-chemical analyzes, in vitro and in vivo.